2014
DOI: 10.5120/18909-0207
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Optimal Placement of DGs and Fixed Capacitor Banks in Radial Distribution Systems using BSA Optimization

Abstract: Nowadays the research on the integration of DG"s and Capacitor banks in radial distribution system is going on, to meet the increased electricity demand and to improve the technical aspects like power loss reduction, voltage profile improvement etc., where the major concerns are finding the optimal sizing of DG"s and Capacitor banks and their locations. This paper presents application of new optimization algorithm; Backtracking Search Algorithm (BSA) to solve the optimal placement of both DG and fixed capacito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Furthermore, numerous other artificial intelligencebased optimization algorithms that have been proposed in literature for the simultaneous DG/SC allocation includes ant lion optimization (ALO) [25], biogeography-based optimization (BBO) [26], backtracking search algorithm (BSA) [27,28], bacterial foraging optimization algorithm (BFOA) [29], binary collective animal behavior optimization (BCAO) [30], binary GSA (BGSA) [31], cuckoo search algorithm (CSA) [32], differential evolutionary algorithm (DEA) [33], discrete imperialistic competition algorithm (DICA) [34], intersect mutation differential evolution (IDME) [35], G best -guided artificial bee colony algorithm (GABC) [36], memetic algorithm (MA) [37], symbiotic organisms search (SOS) [38], tabu search (TS) [39], and teaching-learning-based optimization [40].…”
Section: Existing Research and Itsmentioning
confidence: 99%
“…Furthermore, numerous other artificial intelligencebased optimization algorithms that have been proposed in literature for the simultaneous DG/SC allocation includes ant lion optimization (ALO) [25], biogeography-based optimization (BBO) [26], backtracking search algorithm (BSA) [27,28], bacterial foraging optimization algorithm (BFOA) [29], binary collective animal behavior optimization (BCAO) [30], binary GSA (BGSA) [31], cuckoo search algorithm (CSA) [32], differential evolutionary algorithm (DEA) [33], discrete imperialistic competition algorithm (DICA) [34], intersect mutation differential evolution (IDME) [35], G best -guided artificial bee colony algorithm (GABC) [36], memetic algorithm (MA) [37], symbiotic organisms search (SOS) [38], tabu search (TS) [39], and teaching-learning-based optimization [40].…”
Section: Existing Research and Itsmentioning
confidence: 99%
“…Authors in [35] developed a new hybrid optimization approach based on Artificial Bee Colony (ABC) and Artificial Immune System (AIS) to find the optimal sitting and sizing of DG and SC. In another similar study, the authors suggested a method based on Backtracking Search Algorithm (BSA) to solve the problem of the optimal location of both DG and static capacitor banks for enhance voltage profile and decrease the power loss of distribution system [36].…”
Section: B Literature Reviewmentioning
confidence: 99%
“…It aimed to provide technical, economical, and environmental advantages by using various objective functions (increasing power losses, voltage deviation, energy cost, and gas emissions) with the proposed algorithm. In [23], the Backtracking Search Algorithm (BSA) was used to resolve the integration of DGs and CBs problem. The proposed algorithm results were compared with the GA/PSO, ICA/GA, and AA algorithms in the literature.…”
Section: Introductionmentioning
confidence: 99%